Numerical bounds for the solution of linear systems with symmetric positive definite matrices - Dobner, H. J. (Revista Técnica da Faculdade de Engenharia da de Zulia)
We consider linear systems with symmetric positive definite matrices. For those problems we presenta new melhod for estimating a posteriori the error produced by a numerical solution. The method is especially intended for large sparse systems. This approach has been applied successfully to linear systems arising in process simulation with the conjugate gradient method as underlying scheme.